Editorial - Maya, Mario (Boletín Geológico, 2020)
Boletín Geológico number 46 (2020) publishes three articles on the disciplines of economic geology, hydrocarbon genesis, and basin evolution in several zones of Colombia. The following fragments have been taken from these articles respectively and introduce their contents. The Servicio Geológico Colombiano – SGC has carried out a large geophysical exploration campaign to acquire data and make it available to the academic community and mining industry. The SGC overflew the Andean and eastern part of Colombia and got more than 700,000 km of high resolution airborne geophysical (magnetometry and gamma spectrometry). Moyano et al. present an interpretation of isolated magnetic anomalies located in three different geologic environments in Colombia: San Lucas range, The Andes Cordillera, and the Amazonian craton. Rossello and Saavedra present a discussion about the structural aspects that contribute to the creation of the genetic and morphological characteristics of the bedding surfaces underlying the petrophysical potential of the Matachines field located in the Girardot subbasin, within the Upper Magdalena Valley basin (Valle Superior del Magdalena – VSM), Colombia. The authors focus on sectors where the primary permeability and porosity values are usually too low to meet economic expectations in hydrocarbon exploration or production activities. Rodríguez and Obando report new petrography, total rock chemistry and U-Pb zircon geochronology data of the La Quinta Formation, Serranía de Perijá, at the northern Andes of Colombia. This new information is correlated with other volcano-sedimentary sequences, specifies the distribution of arc volcanism and with the analysis of the inherited zircons in volcanic rocks improves the understanding of the basement distribution on which the arc is founded. The editor acknowledges the efforts of the following reviewers whose comments and recommendations, on the eleven manuscripts submitted, contributed to the improvement of the three articles that were ultimately approved: Ana Ibis Despaigne, Andrés Cárdenas, Ariel Cadena, Barbara Martiny, Camilo Bustamante, César Mora, Germán Bayona, Gustavo Córdoba, Hermann Bermúdez, Hugo Murcia, Jhon Jairo Sánchez, José Luis Arce, Juan Carlos Molano, Juan Diego Colegial, Luis Castillo, Luis Enrique Cruz, Mario Moreno, Mauricio Bermúdez, Umberto Cordani, Natalia Pardo, Oswaldo Ordóñez, Thomas Cramer, and Yamirka Rojas. We recognize the final content of the articles does not necessarily reflect the thoughts of the reviewers and editors.